The effect of cure conditions and temperature changes on the compressive strength of normal and fly ashadded concretes - Esen, Yüksel (My University, 2010)
The aim of this study was to examine compressive strength of fly ash-added concrete and normal concrete cured in water and air and to compare their compressive strength on the 7th, 14th, 21st and 28th days. In addition, the study investigated temperature-induced changes in the compressive strength of concrete samples which completed 28 day cure period. While the compressive strength of concretes cured in air was observed to be higher in early days, it was detected to be higher in concretes cured in water in later days. It was also determined that the compressive strength of fly ashadded concrete was lower than that of normal concrete. In addition, no significant change was observed in the strength of both concrete types at the temperatures up to 400°C, but significant changes were noted over 600°C and the compressive strength of both concrete types decreased by 80% at 800°C. © 2010 Academic Journals.
Keywords: Compressive strength; Concrete; Cure conditions; Elevated temperature; Fly ash